The Role of Digital Technology in Financial Inclusion: A Literature Review and SWOT Analysis - Nurkhalimah, Vera (Generate Digital Publishing, 2025)
Objective: This study aims to explore the impact of digital technology transformation on financial inclusion in the banking sector, focusing on innovations such as fintech, mobile banking, internet banking, e-wallets, blockchain, and artificial intelligence. The objective is to assess how these technologies enhance access to financial services for underserved populations and improve banking efficiency. Research Design & Methods: The research uses a literature review and SWOT analysis to assess the impact of digital technologies on banking. It highlights both the benefits and challenges of digital transformation for financial inclusion, with a focus on infrastructure, digital literacy, cybersecurity risks, and regulatory. Findings: The study finds that digital transformation has enhanced financial inclusion by improving access to services for unbanked and underbanked populations, with innovations like mobile banking and e-wallets reducing costs and boosting efficiency. However, infrastructure gaps, low digital literacy, cybersecurity risks, and outdated regulations remain obstacles to wider adoption. Implications & Recommendations: To maximize the benefits of digital transformation in banking, it is vital to improve digital financial literacy, encourage collaboration among governments, banks, and fintech companies, and address infrastructure gaps. Additionally, updating regulatory frameworks to keep pace with technological advancements is essential for ensuring digital financial services' security and long-term sustainability. Contribution & Value Added: This study enhances the understanding of digital technology's role in financial inclusion, offering practical insights and recommendations for policymakers and industry stakeholders to address challenges and leverage digital transformation for a more inclusive, secure, and sustainable financial ecosystem.